2004
DOI: 10.1007/s00253-004-1807-z
|View full text |Cite
|
Sign up to set email alerts
|

Different control mechanisms regulate glucoamylase and protease gene transcription in Aspergillus oryzae in solid-state and submerged fermentation

Abstract: Solid-state fermentation (SSF) with Aspergillus oryzae results in high levels of secreted protein. However, control mechanisms of gene expression in SSF have been only poorly studied. In this study we show that both glucoamylase (glaB) and protease (alpA, nptB) genes are highly expressed during surface cultivation on wheatbased solid medium, and even higher during cultivation on wheat kernels. In wheat-based liquid medium, low levels of gene expression are observed. Typical SSF cultivation conditions, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 28 publications
1
29
0
2
Order By: Relevance
“…Traditional fermentation of A. oryzae on steamed rice, wheat or soybean generally occurs at 30~35ºC and pH 6.0~6.5 [5,6] and suitable strains have been selected depending on their purpose. In general, solid-phase media is superior to submerged culture for enzyme production by A. oryzae [7][8][9], and some enzymes are exclusively produced by solid-state cultivation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional fermentation of A. oryzae on steamed rice, wheat or soybean generally occurs at 30~35ºC and pH 6.0~6.5 [5,6] and suitable strains have been selected depending on their purpose. In general, solid-phase media is superior to submerged culture for enzyme production by A. oryzae [7][8][9], and some enzymes are exclusively produced by solid-state cultivation [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that transcription of these secretory protease genes was induced when the culture pH changed to neutral pH from acidic pH, suggesting that their transcription is regulated by pH. 20) Our DNA microarray data indicate that the pacC transcript, encoding a transcription factor required for alkaline adaptation, 21) was up-regulated more than 2-fold in the late phase (data not shown), in which pH recovery to neutral was observed (Fig. 1A).…”
Section: Discussionmentioning
confidence: 79%
“…Plasmid pAB4.1 (Hartingsveldt et al 1987) containing the Aspergillus niger pyrG mutant was used as the source of the selection marker. The glucoamylase B gene (glaB) was shown to be highly expressed during solid-state cultivation (Te Biesebeke et al 2005a). Therefore, an expression vector was generated based on glaB expression signals.…”
Section: Methodsmentioning
confidence: 99%